2015
DOI: 10.5796/electrochemistry.83.256
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxide Composition on Structure, Surface Morphology, and Oxygen Evolution Behaviors of IrO<sub>2</sub>-Ta<sub>2</sub>O<sub>5</sub>/Ti Anodes Prepared at a High Temperature

Abstract: Catalytic coatings comprising a mixture of IrO 2 and Ta 2 O 5 were prepared at 50-80 mol% Ir by thermal decomposition at 470°C, and the crystallographic structures and surface morphologies were investigated. XRD analysis and high-resolution SEM observation using low accelerated incident beam revealed that decreasing Ir ratio made a phase transition of IrO 2 from crystalline to partly amorphous, and nano IrO 2 particles of 10 nm or less and nano chains made of them, which were uniformly dispersed on the flat ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 47 publications
2
23
1
Order By: Relevance
“…Many cracks were observed for the sintered IrO 2 -Ta 2 O 5 layer on the Ti plate. The mud cracked feature is typical for DSA. ,, The cracks surround a smooth and flat area. On the other hand, the mud cracks were few in the case of IrO 2 -Ta 2 O 5 /Ti felt samples (see also Figure S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many cracks were observed for the sintered IrO 2 -Ta 2 O 5 layer on the Ti plate. The mud cracked feature is typical for DSA. ,, The cracks surround a smooth and flat area. On the other hand, the mud cracks were few in the case of IrO 2 -Ta 2 O 5 /Ti felt samples (see also Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…However, the stability was not enough for long-term operation in acidic environments such as H 2 SO 4 and HClO 4 solutions at the high anodic potential. , Considering both activity and stability, iridium oxide (IrO 2 ) is the best catalytic component for OER in acidic sulfate solution. The defective IrO 2 and amorphous Ir oxide/hydroxide have reportedly exhibited higher OER activity than crystalline IrO 2 . Among the IrO 2 -based anodes, the mixed layer of IrO 2 (70 mol % Ir) and tantalum oxide (Ta 2 O 5 , 30 mol % Ta) coated on titanium (Ti) electrode is the best OER electrocatalyst in terms of the high activity and the long-term durability. , The layers of noble metal oxide dispersed in the nonprecious metal oxide on the Ti substrate are frequently referred to as dimensionally stable anodes (DSA), which are widely used in the industrial electrochemical processes such as the chlor-alkali process and electrolytic refining. ,, The electrocatalytic activity of IrO 2 -Ta 2 O 5 coated on Ti electrodes is significantly affected by the chemical composition and calcination conditions. ,,,, …”
Section: Introductionmentioning
confidence: 99%
“…FOCUS) was used to analyze those samples, and the surface morphology was observed using high-resolution SEM (ZEISS, Model SUPRA M 55VP) with two different modes. The high-voltage mode used a normal SE detector and an incident electron beam of 15 keV acceleration voltage, and the low-voltage mode used an in-lens SE detector and 1 keV as previously described 4) , 5) . Such a low acceleration voltage is advantageous for suppressing the penetration of the electron beam into the oxide coating, i.e., the penetration depth at 1 keV is 5 nm, which is about 1/8 at 15 keV 6) ; so that the SEM image at 1 keV is limited to the information of the outermost surface 7) ,8) .…”
Section: Methodsmentioning
confidence: 99%
“…While the mixture of PbO2 and PbSO4 deposited on the anode can be analyzed by X-ray diffraction (XRD) to detect the existence, it is difficult to show their surface distribution by conventional elemental analysis methods such as energy dispersive X-ray analysis (EDX) , because the energies of characteristic X-rays of Pb Mα and S Kα peaks are very close (Pb Mα=2.350 keV, S Kα=2.308 keV) . On the other hand, we have also reported that the nano-structured IrO2 particles dispersed in the amorphous Ta2O5 matrix are successfully distinguished on secondary electron microscope (SEM) images obtained at low acceleration voltage like 5 keV or lower 4) , 5) . In this paper, the results by the same technique applied to distinguish conductive PbO2 and non-conductive PbSO4 deposited on IrO2-Ta2O5/Ti anodes are shown, and the benefit of using low accelerated incident electron beams and the in-lens secondary electron detector is reported.…”
Section: Introductionmentioning
confidence: 97%
“…12,13 Nano-sized IrO 2 catalysts have also been reported to have high OER activity due to the increase in the electrochemically active surface area (ECSA). 10,[14][15][16] We have successfully improved the activity of the IrO 2 -Ta 2 O 5 by using sintered Ti fibers with a three-dimensional (3D) porous structure (Ti felt, Fig. S1 of the Supporting Information) instead of the conventional Ti substrate, which is a geometrically flat and dense plate.…”
Section: Introductionmentioning
confidence: 99%